Effect of oocyte collection techniques and maturation media on in vitro maturation of buffalo oocytes - CHAUDHARI, C F; DERASHRI, H J; CHAUDHARY, SANDHYA S; PURI, GOPAL; MODI, L C (The Indian Journal of Animal Sciences, 2014)
The study was conducted to know the effect of oocyte collection techniques and various maturation media on in vitro maturation of buffalo oocytes obtained from slaughterhouse derived ovaries. Highest maturation rate was observed in TCM 199 + FBS + hCG media, followed by Ham’s F-10 + FBS + hCG, TCM 199 and Ham’s F-10 alone. The difference between them was statistically nonsignificant. Maturation rate was significantly higher in oocytes collected by aspiration than by slicing technique. Nonsignificant difference was observed in maturation rates in BCB+ and BCB– oocytes. In conclusion, addition of sera and hormones into basic maturation media, viz. TCM-199 and Ham’s F-10 resulted into better in vitro maturation rate.